The Design of Decision Support Model for Housing Purchasing Decision Making Problem (S/O 13868) - Mohd Sappri, Mazlan; Omar, Mohd Faizal; Mohd Nawi, Mohd Nasrun; Nursal, Ahmad Taufik (UUM, 2020)
Housing purchasing decision making process is complex decision making process. With involvement of large pool criteria, numerous of delay and abandon housing project, and also high investment have increased decision difficulties from time to time. Effective decision support tools are crucial towards a better housing purchasing decision. Multi attribute decision making (MADM) is generally recognised as a valuable decision support for structuring housing purchasing decision making problem. However to date, existing MADM model are less effective for homebuyerS who has limited infonnation and knowledge in housing purchasing. This research has implemented users generate online properties information in housing purchasing decision making process. Literature review revealed great numbers availability of online user generate infonnation has significantly influenced consumer purchasing behaviour especially in high stake purchasing decision. This infonnation has been addressed as User Generate Infonnation (UGI). Thus, a decision support model incorporated Fuzzy TOPSIS and Sentiment Analysis (SA) for the evaluation of homebuyers needs and UGI in housing purchasing decision making. Multiple real house projects in Penang, Malaysia were used for testing, application and validation of the proposed decision model. Findings shown the proposed is usable and highly potential for solving housing purchasing. Thus, this research has demonstrated a purposeful decision framework that is applicable in purchasing decision, especially high stakes purchasing decision.